Analysis of discharge performed by the COVID-19 remote monitoring team in the City of Piauí (Research, Society and Development, 2020)
The objective of the study is to present epidemiological data related to the closure of the first 197 cases of the remote monitoring service for patients with confirmed cases of COVID-19 in the city of Parnaiba-PI. It is a quantitative epidemiological study that followed approximately 950 patients with suspected cases of COVID-19 for 2 months, with epidemiological confirmation of 197 cases, where 196 of them were discharged from the service and 1 died. Analyzing the data of the patients who were discharged, it was observed that there was no difference in terms of gender distribution, the most affected age group was between 20 and 40 years and that most individuals did not have any associated comorbidity. Of the total number of patients, 142 underwent pharmacological treatment, of which only 26 had any side effects. The results obtained regarding the frequency of side effects were similar to data in the literature, as well as the incidence of frequency of symptoms also showed similarities in relation to data in the world literature. Of the total number of patients analyzed in the study, only 5 patients required hospitalization, showing that the syndromic surveillance system showed good results, being a way to intervene early and reduce the risk of worsening the disease.